Squamous cell carcinoma antigen as a prognostic marker and its correlation with clinicopathological features in head and neck squamous cell carcinoma: Systematic review and meta-analysis - Travassos, Daphine Caxias [UNESP]; Fernandes, Darcy [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Navarro, Cláudia Maria [UNESP]; Bufalino, Andreia [UNESP] (Wiley, 2018)
Background: Several studies investigate the prognostic value of squamous cell carcinoma antigen (SCC-Ag) in head and neck squamous cell carcinoma (HNSCC) patients, with contradicting findings. Considering this, the aim of this study was to evaluate the prognostic value of high SCC-Ag levels and its association with clinicopathological features of HNSCC. Material and Methods: PubMed, SCOPUS, and Cochrane Library were searched for relevant studies up to December 2015. English-language publications assessing clinicopathological features of HNSCC and the prognostic significance of SCC-Ag in this disease were included. A meta-analysis was performed using Review Manager 5.3 and STATA version 14 software to clarify a possible association between SCC-Ag and clinical outcomes. Results: A total of 11 studies met inclusion criteria, comprising 1901 cases of HNSCC. The results of the meta-analysis showed that there was significant correlation between high SCC-Ag levels and males (odds ratio [OR]=2.99, 95% CI: 1.18-7.57, P=.02 fixed-effect), and advanced TNM stages (OR=3.18, 95% CI: 1.88-5.38, P<.0001 random-effect). The survival meta-analysis showed a pooled hazard ratio for disease-free survival (DFS) and overall survival (OS) of 1.01 (95% CI: 0.70-1.31) and 0.86 (95% CI: 0.54-1.17), respectively. Conclusion: Our meta-analysis suggests that elevated SCC-Ag levels have a significant correlation with males and TNM stage, but may not be used as predictive marker for OS and DFS in HNSCC patients.
Keywords: head and neck squamous cell carcinoma; meta-analysis; prognosis; squamous cell carcinoma antigen; tumor markers